Shared Storybook Reading and Oral Language Development: A Bioecological Perspective - Grolig, Lorenz (Frontiers in Psychology, 2020)
Shared reading research has become increasingly multidisciplinary and has incorporated a multitude of assessment methods. This calls for an interdisciplinary perspective on children’s shared reading experiences at home and at the child care center, and relationships to their oral language development. Here, we first discuss Bronfenbrenner’s bioecological model of human development (Bronfenbrenner & Morris, 2006) regarding the relationship between shared storybook reading and oral language development. Second, we develop a framework for investigating effects of shared reading on language development in two important microsystems: the home literacy environment and the child care literacy environment. Zooming in on shared storybook reading as a proximal process that drives oral language development, we then develop a triad model of language learning through shared storybook reading that integrates approaches and evidence from educational psychology, developmental psychology, psycholinguistics, and corpus linguistics. Our model describes characteristics of children, adults, and books, and how their interplay influences shared reading activities. Third, we discuss implications for the Home Literacy Model (Sénéchal & LeFevre, 2002, 2014) regarding the conceptualization of shared reading as an important source of oral language development. Finally, to facilitate integrated research designs that include the two most important microsystems, we provide a critical discussion of assessment methods used in research that investigates the home literacy environment and the child care literacy environment and relate them to the shared reading triad in our bioecological model of shared storybook reading. We conclude with directions for future research.